Development, deployment and experimental test on the novel tethered system GEM for tidal current energy exploitation. (December 2017) - Coiro, D.P.; Troise, G.; Scherillo, F.; De Marco, A.; Calise, G.; Bizzarrini, N.
Abstract: This paper presents the development of the innovative device GEM (Generatore Elettrico Marino, Marine Electrical Generator), designed to harness tidal current energy. The device, also known as Ocean's kite, consists of a submerged floating structure (made of two separate hulls) linked to the seabed by means of a tether. The floating body supports two counter-rotating ducted turbines exposed to the flow and mounted sideways. Electrical generators are installed behind each of the two rotors and all auxiliary systems are housed within the hulls of the main floating bodies. Both a reduced-scale model of the whole GEM system and its isolated components were tested in the towing tank facility of the University of Naples. Data collected during this experimental campaign will be presented here. The analysis of static and dynamic behaviour of the system will be discussed as well. Finally, the deployment of a full-scale prototype of GEM in the Venetian lagoon and some experimental results will be illustrated. Highlights: Tests on GEM, ocean kite system for marine currents energy conversion, are presented. Towing tank tests on bare and shrouded hydro-turbine rotor are reported. The GEM device is self-orienting and easy to install and maintain. Normal and off-design operating conditions of the GEM have been considered. Tests on a 100 kW GEM prototype deployed in Venice lagoon are reported.